Pertanggung Jawaban Korporasi Dalam Tindak Pidana Pencucian Uang - Prakasa, Ragil Surya; Rahmadayanti, Indah; Yolanda , Jelfidha Sukma; Febrianis , Ririn; Farhan , Muhammad Adila; Amanda , Shakira; Pratama , Okta Adi (ASOSIASI IDEBAHASA KEPRI, 2024)
The crime of money laundering or what is better known as money laundering is a term that is often heard in various mass media, therefore many understandings have developed regarding the term money laundering. Sutan Remi Sjahdeini emphasized that currently the term money laundering is commonly used to describe efforts carried out by individuals or legal entities to legalize